An Analysis of Women’s Electoral Participation in Nigeria’s 2011 and 2015 General Elections in Ado-Odo/Ota Local Government Area, Ogun State, Nigeria (Journal of Management and Social Sciences, 2017)
AbstractGlobally, women are marginalised and grossly underrepresented in the area of public life where important decisions which affect their lives are taken. Interestingly the trend still persists. The study examined the trend of women’s electoral behaviour between 2011 and 2015 using Ado-Odo/Ota Local Government Area of Ogun State as the study area. Descriptive survey design was used with data collected through questionnaire, indepth and key informant interviews. Findings revealed that women’s participation in electoral politics is highly observable only at the spectatorial and transitorial levels. Climbing the electoral ladder and expressing themselves as political gladiators remain difficult for many of them. While women have participated actively in electoral politics, such participation has been as voters and support staff. They are however not rewarded with positions of power in political parties. Political party and legislative gender quotas should be adopted to immediately enhance the attempt of women at becoming political gladiators. Keywords  Election, electoral behaviour, politics, women